2018
DOI: 10.1002/jrs.5534
|View full text |Cite
|
Sign up to set email alerts
|

Study of dry‐ and wet‐process amorphous arsenic sulfides: Synthesis, Raman reference spectra, and identification in historical art materials

Abstract: This paper reports the dry and wet synthetic procedures and characterization by Raman spectroscopy of amorphous arsenic sulfide reference pigments. Reference spectra of two amorphous materials obtained by wet process methods and four dry process references of amorphous arsenic sulfide pigments of known composition are presented and discussed.While all materials present a main band characteristic for the amorphous pigment centered on 341 cm −1 , additional small contributions indicate the presence of sulfur, ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 42 publications
4
21
0
Order By: Relevance
“…The comparison with spectra published in recent literature (see, for example, Grundmann and Richter, Vermeulen et al, and Vermeulen et al) showed a good correspondence between our spectra and those from samples recently classified as arsenic sulfide glass . As reported by Vermeulen et al, the broad band at 340 cm ‐1 corresponds to the Raman shift of the As‐S‐As stretching vibration in AsS 3 in amorphous arsenic sulfide pigments, whereas those at 186 and 233 cm ‐1 are attributable to realgar‐like crystalline nano‐phases embedded in the amorphous matrix.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…The comparison with spectra published in recent literature (see, for example, Grundmann and Richter, Vermeulen et al, and Vermeulen et al) showed a good correspondence between our spectra and those from samples recently classified as arsenic sulfide glass . As reported by Vermeulen et al, the broad band at 340 cm ‐1 corresponds to the Raman shift of the As‐S‐As stretching vibration in AsS 3 in amorphous arsenic sulfide pigments, whereas those at 186 and 233 cm ‐1 are attributable to realgar‐like crystalline nano‐phases embedded in the amorphous matrix.…”
Section: Resultssupporting
confidence: 88%
“…Moreover, although the naturally occurring mineral forms of arsenic sulfides are well studied (see Grundmann and Richter and Bonazzi et al), their artificially manufactured equivalents are largely unexplored, and often no difference between natural and artificial sulfides is made in the literature. Recent investigations involving both the analysis of pigmented artefacts and the experimental preparation of pigment powders and cakes according to the historical recipes are finally clarifying the nature, production, and use of artificial arsenic pigments …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The spectra for these particles also showed minor bands at ca. 233 and 495 cm −1 , which are attributed to realgar-like nano phase and are considered to be indicative of a heat process used to produce the amorphous pigment [51]. This hypothesis was also supported by the fact that some other particles in these samples showed mixed features between natural orpiment and amorphous arsenic sulfide.…”
Section: Yellowmentioning
confidence: 56%
“…This hypothesis was also supported by the fact that some other particles in these samples showed mixed features between natural orpiment and amorphous arsenic sulfide. These observations can be taken as indication of the production of amorphous arsenic sulfide by sublimation of natural orpiment [50,51].…”
Section: Yellowmentioning
confidence: 99%